2008
DOI: 10.1159/000127449
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Basis for the Differentiation Potential of Mesenchymal and Embryonic Stem Cells

Abstract: Stem cells have the ability to self-renew, and give rise to one or more differentiated cell types. Embryonic stem cells can differentiate into all cell types of the body and have unlimited self-renewal capacity. Somatic stem cells are found in many adult tissues. They have an extensive but finite lifespan and can differentiate into a more restricted range of cell types. Increasing evidence indicates that the multilineage differentiation ability of stem cells is defined by the potential for expression of develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 130 publications
(178 reference statements)
0
17
0
Order By: Relevance
“…While CpG methylation is a well-studied epigenetic modification to DNA, research indicates poor correlation between gene expression and promoter methylation, suggesting that other epigenetic mechanisms may also be important determinants for lineage preference (77, 81, 83). Additionally, many studies have discovered general hypomethylation of lineage-specific promoter regions in mesenchymal and non-mesenchymal ASCs, regardless of origin (61, 84, 85).…”
Section: Mechanistic Explanations Of Niche Specific Lineage Preferencmentioning
confidence: 99%
“…While CpG methylation is a well-studied epigenetic modification to DNA, research indicates poor correlation between gene expression and promoter methylation, suggesting that other epigenetic mechanisms may also be important determinants for lineage preference (77, 81, 83). Additionally, many studies have discovered general hypomethylation of lineage-specific promoter regions in mesenchymal and non-mesenchymal ASCs, regardless of origin (61, 84, 85).…”
Section: Mechanistic Explanations Of Niche Specific Lineage Preferencmentioning
confidence: 99%
“…Several published scientific investigations have discussed short comings or potential negative effects on the viability and proliferative ability of cells associated with the use of centrifugal force to concentrate MSCs from native bone marrow cells or to expand the number of MSCs through ex vivo culturing techniques [15,[39][40][41][42][43][44][45][46][47][48][49]; other related concerns include potential for genetic/epigenetic alterations, transfer of zoogenic diseases to recipient host, contamination and loss of critical key cells present in the original naturally balanced bone marrow niche microenvironment [49][50][51]. Thorough understanding of the impact of various culture media compositions and culturing parameters (e.g., temperature, seeding densities, and type of mechanical agitation during culturing) on the viability and proliferative status of bone marrow MSCs that will be used for regenerative medicine applications is very important.…”
Section: Potential Adverse Effects Of Centrifu-gal Force Cell Culturmentioning
confidence: 99%
“…For example, changes in gene expression without a change in DNA sequence can occur due to epigenetic forces. With respect to stem cells, there is an increasing body of evidence for an epigenetic basis for pluripotency and differentiation potential [49][50][51]. As the precise epigenetic mechanisms are currently not well understood, it is important to recognize and possibly identify the centrifugal/bioprocess conditions that can significantly influence the epigenome, and thus affect the safety and efficacy of MSCs used for injection regenerative therapy.…”
Section: Potential Adverse Effects Of Centrifu-gal Force Cell Culturmentioning
confidence: 99%
“…Genome-wide chromatin immunoprecipitation (ChIP) analysis that has been performed independently by several groups has revealed that large areas of repressive histone modification of methylated lysine 27 of histone 3 (H3 K27me) intermingle with smaller regions of permissive chromatin marked by methylated lysine 4 (H3K4me) at highly conservative non-coding elements (HCNE). These Bbivalent domains^allow important transcription factor genes to be poised for rapid transcriptional activation upon differentiation (Collas et al 2008). Therefore, epigenetic analysis of neuraldifferentiation-associated marker genes of MSCs is an important issue that should be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%